Optimized Extraction of Glycoproteins from Ganoderma lucidum - Naomi Tritean; Ștefan-Ovidiu Dima; Anisoara Cimpean; Diana Constantinescu-Aruxandei; Florin Oancea (Chemistry Proceedings, 2022)
Ganoderma mushrooms are a valuable source of bioactive compounds [...]